2014
DOI: 10.1037/a0037777
|View full text |Cite
|
Sign up to set email alerts
|

Tool morphology constrains the effects of tool use on body representations.

Abstract: What factors constrain whether tool use modulates the user's body representations? To date, studies on representational plasticity following tool use have primarily focused on the act of using the tool. Here, we investigated whether the tool's morphology also serves to constrain plasticity. In 2 experiments, we varied whether the tool was morphologically similar to a target body part (Experiment 1, hand; Experiment 2, arm). Participants judged the tactile distance between pairs of points applied to their tool-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
203
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 103 publications
(237 citation statements)
references
References 66 publications
(147 reference statements)
29
203
4
1
Order By: Relevance
“…These results suggests that tactile spatial remapping relies on a representation of the hand which is fatter than actual hand shape, consistent with results reported previously for position sense , 2012aLongo et al, 2012) and tactile size perception (Canzoneri et al, 2013;Green, 1982;Le Cornu Knight et al, 2014;Longo & Sadibolova, 2013;Miller, Longo, & Saygin, 2014). 1.…”
Section: Results and Discussion Internal Configuration Of Responsessupporting
confidence: 90%
“…These results suggests that tactile spatial remapping relies on a representation of the hand which is fatter than actual hand shape, consistent with results reported previously for position sense , 2012aLongo et al, 2012) and tactile size perception (Canzoneri et al, 2013;Green, 1982;Le Cornu Knight et al, 2014;Longo & Sadibolova, 2013;Miller, Longo, & Saygin, 2014). 1.…”
Section: Results and Discussion Internal Configuration Of Responsessupporting
confidence: 90%
“…Touch, however, can clearly also be used to perceive the extrinsic physical properties of objects. Longo, Azañón, and Haggard (2010) argued that perceiving the metric properties of objects touching the skin requires that immediate sensory signals be combined with (Berryman, Yau, & Hsiao, 2006), sounds produced by action (Tajadura-Jiménez et al, 2012, 2015, the rubber hand illusion (Bruno & Bertamini, 2010), and tool use (Canzoneri et al, 2013;Miller, Longo, & Saygin, 2014, 2017. Thus, in analogy with the modulation of perceived passability of apertures when apparent eyeheight was altered shown by Warren and Whang (1987), these results show that experimental manipulations of represented body size alter perceived tactile distance.…”
Section: Statement Of Public Significancementioning
confidence: 91%
“…Other recent research has shown that perceived tactile distance is expanded across joint boundaries, showing that the high-level segmentation of the body into discrete parts produces categorical perception effects on tactile distance (de Vignemont, Majid, Jola, & Haggard, 2009;Le Cornu Knight, Longo, & Bremner, 2014). Finally, two recent studies have shown that tool-use, which can be thought of as extending arm size, also produces systematic changes to tactile distance perception (Canzoneri et al, 2013;Miller, Longo, & Saygin, 2014).…”
Section: Distortions In Tactile Size Perceptionmentioning
confidence: 99%